2015
DOI: 10.1515/cpe-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Process of Hydraulic Mixing in Anaerobic Digester of Biogas Plant

Abstract: Two systems of hydraulic mixing in a vertical cylindrical anaerobic digester: standard and modernised are discussed in the paper. Numerical investigations that were carried out are focused on a study of hydrodynamic processes in an aerobic digester using two various systems of hydraulic mixing as well as on analysis of the efficiency of methane fermentation process accomplished under different geometric parameters of an anaerobic digester and systems of hydraulic mixing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Currently, the design and development of a laboratory-analytical complex for studying the processes of anaerobic digestion on a semi-industrial scale with a hydraulic mixing system [64], as well as subsequent thermochemical conversion of the digestate [65], is underway. It is planned to use a cavitation reactor for the pre-treatment of agricultural waste.…”
Section: P R =mentioning
confidence: 99%
“…Currently, the design and development of a laboratory-analytical complex for studying the processes of anaerobic digestion on a semi-industrial scale with a hydraulic mixing system [64], as well as subsequent thermochemical conversion of the digestate [65], is underway. It is planned to use a cavitation reactor for the pre-treatment of agricultural waste.…”
Section: P R =mentioning
confidence: 99%
“…Numerous studies can be found which include the optimization of the impeller design and the mixing speed of the impeller [10][11][12][13][14][15]. Singh et al [6,9] compared the various designs, which were used for the optimization of mixing in the digester.…”
Section: Introductionmentioning
confidence: 99%